Research into the reading process of the academic community of the old Vilnius University: aspects of historiography - Krakytė, Asta (Knygotyra, 2006)
The article provides a general overview of the research into the reading process of the academic community of Vilnius University in 1579–1832 derived from significant research in librarianship and book science. It presents sources and strategies to reveal the multifaceted relations existing between literature, the reader, priorities, the environment, results, etc. This article also analyzes works in humanities and social sciences with significantly reliable data related to particular aspects of the issue. After investigating works of Lithuanian and Polish scientists M. Brensztejn, L. Piechnik, M. Biržiška, L. Vladimirovas, P. Rabikauskas, D. Kuolys, etc., and comparing their deductions, it was observed that reading at Vilnius University in 1579–1832 was influenced by programs of sciences and official regulations of the Jesuit order no less than by local conditions. It is important to emphasize the remarkable influence of the characteristic classical model of education, applied at the University since 1579 and based on the learning of Latin, Greek, and Hebrew language. Some changes were made to the local system of education since the middle of the 18th century due to the influence of the Piar order, but Jesuit authority directed the institution until 1832. Referred articles show that the process of education in Vilnius University was intended to promote a high level of maturity of the reader. During the process of learning new languages, students went through different stages of reading, improving their skills by interpretation and analysis. This was further cultivated in disputations, theatre performances, and promoted by creating new texts, especially occasional publications. This process is reflected in numerous publications and manuscripts written by professors and students. Data accumulated in referred articles show that the usage of literature by the academic community was influenced by books collated by University Library and traditional values common for the establishment of higher education for all parts of Europe that were under the leadership of the Jesuit order. In spite of the fact that the main part of reading sought by academic society was composed of professional literature, professors of Vilnius University were distinguished by rather broad reading interests typical to well-educated persons of their time and assimilated humanistic ideals embedded in Vilnius University by the Jesuit order. Although there are many ways to solve present-day issues of categorizing the reading process, material, strategies, etc., sufficient attention to historical approaches has not been given in Lithuania. Many investigations into this area do not reveal the situation well. Yet, even selected quality research into this process can provide us with new directions for research and decision-making, and can increase our knowledge of the development, tendencies, and culture of reading in all of Lithuania during the 16th–19th centuries.